2018
DOI: 10.1002/jrs.5464
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the degradation mechanism of cellulose nitrate in cinematographic films by Raman microscopy

Abstract: The degradation of cellulose nitrate cinematographic films stored inside an aluminum can was studied by infrared spectroscopy and Raman microscopy. Cellulose nitrate image heritage is strongly susceptible to degradation, being a major conservation challenge. Infrared spectroscopy has been the traditional technique in the assessment of the polymer degradation, but new in situ diagnostic tools to monitor the initial stages of degradation are needed. In this work, cellulose nitrate films were produced and irradia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 20 publications
1
26
0
Order By: Relevance
“…The films present inside are in an advanced stage of degradation, with tacky emulsion, loss of image and intense noxious smell. These films have already been studied in a published work by infrared and Raman spectroscopies [31].…”
Section: Cinematographic Films From the National Archive Of Motion Pimentioning
confidence: 99%
See 1 more Smart Citation
“…The films present inside are in an advanced stage of degradation, with tacky emulsion, loss of image and intense noxious smell. These films have already been studied in a published work by infrared and Raman spectroscopies [31].…”
Section: Cinematographic Films From the National Archive Of Motion Pimentioning
confidence: 99%
“…1. At time 0, both spectra are characterized by the stretching of the CH and CH 2 bonds between 2900 and 3000 cm −1 ; the strong nitrate vibration bands (μFTIR: 1653, 1280 and 840 cm −1 ; ATR-FTIR: 1636, 1274 and 827 cm −1 ); the cellulosic vibrational envelope between 1200 and 900 cm −1 [31]. A decrease in DS leads to a decrease of the nitrate groups absorbance and an increase of the hydroxyl band (3700 -3000 cm −1 ), evolving towards the spectrum of cellulose, Fig.…”
Section: Cellulose Nitrate Calibration Curvesmentioning
confidence: 99%
“…In situ identification of additives within historic polymeric objects has been most successfully demonstrated using Raman spectroscopy; including the use of a portable dispersive instrument (excitation at 785 nm) and laboratory-based FT-Raman instruments (excitation at 1064 nm) [111][112][113]. Using a portable spectrometer to survey historic aviation glasses, Madden et al identified camphor in CN, alongside dimethyl phthalate, diethyl phthalate and TPP in CA.…”
Section: Qualitative and Quantitative Methods For The Analysis Of Plamentioning
confidence: 99%
“…7). Cellulose nitrate is the polynitrate ester of cellulose with a typical 2.2-2.8 nitrate groups per glucose unit within the structure (Neves et al 2019). Cellulose nitrate properties and applications depend on the degree of nitration.…”
Section: Cellulose Nitratementioning
confidence: 99%